Spanning Trees of Lattices Embedded on the Klein Bottle - Fuliang Lu (The Scientific World Journal)
The problem of enumerating spanning trees in lattices with Klein bottle boundary condition is considered here. The exact closed-form expressions of the numbers of spanning trees for 4.8.8 lattice, hexagonal lattice, and 33·42 lattice on the Klein bottle are presented.